Show that substituting y = xv, where v is a function of x, in the differential equation "xy(dy/dx) + y^2 − 2x^2 = 0" (with x is not equal to 0) leads to the differential equation "xv(dv/dx) + 2v^2 − 2 = 0"

This is the first part of a Step 1 question (2012 question 8), and is fairly typical in that it requires A Level Maths understanding to be applied in a number of different ways, out of the usual context.We begin by finding a new expression for (dy/dx), in terms of v. We do this by differentiating "y = xv", and getting:dy/dx = x(dv/dx) + vBy substituting this and "y = xv" into the original differential equation, we get:(x)(xv)(x(dv/dx) + v) + (xv)^2 - 2(x^2) = 0(x^3)v(dv/dx) + 2(xv)^2 - 2(x^2) = 0We can divide by x^2, since we know that x does not equal zero. This gives the required result:xv(dv/dx) + 2(v^2) - 2 = 0The rest of the question first asks you to find a solution to the original equation. The new equation is now separable, and can be solved to find v. This can be substituted back into "y = xv", giving a solution for y. Try it if you like. It should look something like:(x^2)(y^2 - x^2) = C (where C is a constant)The question then asks you to solve (again with x is not equal to zero):y(dy/dx) + 6x + 5y = 0This can be done with the same substitution, which again makes it separable. Using partial fractions, integrating, finding v in terms of x (or vice versa), and substituting allows a solution to be found. This should (although it is still pretty ugly, particularly on a computer screen) look like:((y + 3x)^3)/((y + 2x)^2) = B (where B is a constant)

Answered by Will W. STEP tutor

9814 Views

See similar STEP University tutors

Related STEP University answers

All answers ▸

How would you prove the 'integration by parts' rule?


Suppose that 3=2/x(1)=x(1)+(2/x(2))=x(2)+(2/x(3))=x(3)+(2/x(4))+...Guess an expression, in terms of n, for x(n). Then, by induction or otherwise, prove the correctness of your guess.


(x_(n+1), y_(n+1))=(x_n^2-y_n^2+a, 2x_ny_n +b+2). (i) Find (x1, y1) if (a, b)=(1,-1) and (x_n, y_n) is constant. (ii) Find (a, b) if (x1, y1)=(-1,1) and (x_n, y_n) has period 2.


Let p and q be different primes greater than 2. Prove that pq can be written as difference of two squares in exactly two different ways.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences